Prediction of kraft lignin extraction performance using emulsion liquid membrane carrier-diffusion model - Yan, Channyuk (Penerbit UTM Press, 2014)
This study presents the model to predict the performance of emulsion liquid membrane (ELM) to extract kraft lignin. Kraft lignin is one of the raw material that can be convert into biodiesel and also applied in producing large amount of chemical product such as vanillin. ELM is a separation method which can separate component without mechanical support. In this study, ELM model was developed and solved using MATLAB software. Three parameters were investigated in this study such as treat ratio, carrier concentration and initial concentration of feed phase. The study shows that ELM performs best at treat ratio of 1:5, concentration carrier of 0.3M and 0.5g/L of initial concentration of feed phase.